A novel method based on meta-learning for bearing fault diagnosis with small sample learning under different working conditions. (15th April 2022) - Su, Hao; Xiang, Ling; Hu, Aijun; Xu, Yonggang; Yang, Xin
Highlights: A novel method called DRHRML is proposed for bearing fault diagnosis with small samples under different working conditions. Improved sparse denoising autoencoder (ISDAE) is proposed to preprocess the raw vibration data. Two novel task datasets are constructed for verifying the proposed method. Abstract: Recently, intelligent fault diagnosis has made great achievements, which has aroused growing interests in the field of bearing fault diagnosis due to its strong feature learning ability. Sufficient bearing fault samples are taken for granted in existing intelligent fault diagnosis methods generally. In practice, however, the lack of fault samples has been a knotty problem. Therefore, in this paper, a novel method called data reconstruction hierarchical recurrent meta-learning (DRHRML) is proposed for bearing fault diagnosis with small samples under different working conditions. This approach contains data reconstruction and meta-learning stages. In the data reconstruction stage, noise is reduced and the useful information hidden in the raw data is extracted. In the meta-learning stage, the proposed method is trained by a recurrent meta-learning strategy with one-shot learning way. This approach is demonstrated on the bearing fault database with 92 working conditions from Case Western Reserve University and with 56 working conditions from laboratory. Results show that the proposed method is effective for bearing intelligent fault diagnosis with small samples under different working conditions.